OWNING YOUR PROJECT-BASED LEARNING the college student's guide to design thinking, problem... selection, and self-assessment. - Preston, Jacqueline ([S.l.] : ROUTLEDGE, 2025)
Owning Your Project-Based Learning is a user-friendly, vividly illustrated guide designed to help undergraduate students and their instructors fully realize the power of project-based learning (PBL). This book complements a wide range of discipline-specific materials, guiding college students to identify topics of interest, conduct thorough research, and tackle real-world problems through thoughtfully designed projects. It is an indispensable resource for undergraduate instructors, enabling them to focus on content while providing students with the necessary tools to collaborate with community partners and effectively manage project development. Whether assigned by a professor or developed with teams or community partners, PBL offers enriching, hands-on educational experiences across various disciplines. As the demand for PBL at the undergraduate level increases, this essential guide addresses college-specific needs from the academic research process to the critical roles of distribution, publication, and multimedia in career readiness ensuring comprehensive support for both students and faculty.
Keywords: Project method in teaching; EDUCATION / Curricula; EDUCATION / Aims & Objectives; EDUCATION / Higher